MENINGKATKAN HASIL BELAJAR LEMPAR CAKRAM MELALUI PEMBELAJARAN INQUIRI - Hermanto, Hermanto; Triansyah, Andika; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractProblems identification (1) teachers only focus on direct learning methods and do    not try to use new learning methods. (2) students do not focus on paying attention to learning that takes place, because students are busy with their respective activities. (3) learning becomes ineffective because students get bored quickly with learning methods such as direct learning. The purpose of this study was to determine that there was an increase in learning outcomes of discus throwing through. The research method  used was Classroom Action Research (CAR). The data obtained was the value of skills in pre-cycle with a value of 59, the percentage of classical completeness 26% Cycle I with a value of 71, the percentage of classical completeness 50% cycle II with a value of 87% classical completeness 85% and the value of knowledge in pre-cycle with a value of 63, the percentage of classical completeness 24% cycle I with a value of 74, the percentage of completeness of classical 44% cycle II a value of 87 percentage of classical completeness of 85%. It can be concluded that cycle II action the learning outcomes of students through inquiry learning have fulfilled the criteria. Keywords: Inquiry Learning, Learning Outcomes of Discus Throwing